Structural components of formation of future bachelors in physical education and sports for coaching activity - Zaiets Dmytro (Бердянський державний педагогічний університет, 2020)
In the article, the structural components of the formation of future bachelors in physical culture and sports of coaching, corresponding pedagogical functions and indicators on the basis of the scientific literature analysis are determined. The structural components include: cognitive and creative, design and diagnostic, organizational, informative and communicative, analytical components. It is stated that the cognitive and creative component is realized through educational, cognitive, research, creative functions. The informative and communicative component is realized through informative, communicative, perceptual, interactive, suggestive, stimulating functions. The design and diagnostic component is implemented through diagnostic, prognostic, design and modeling functions. The organizational component is implemented through organizational, managerial, controlling, guiding functions. The analytical component is implemented through: evaluative, analytical, corrective functions. It is determined that the reflexive function is common to all components of the coaching. It is determined that the indicator of the formation of the cognitive and creative component is general pedagogical, special, coaching knowledge; motivation for educational and cognitive activity; value attitude to professional activity; ability for professional creativity. An indicator of the formation of informative and communicative component is the ability of didactic processing of educational material; mastering methods of education and training; possession of pedagogical communication styles. An indicator of the formation of the design and diagnostic component is the ability to carry out sports and pedagogical diagnostics, the ability to design and model the training process. An indicator of the organizational component formation is the ability to organize, direct, control the training process; possession of sports and pedagogical technologies; adequate professional evaluation and self-assessment; ability to adjust the results of professional and pedagogical activity; knowledge of evaluation of the achieved results. Adequate professional evaluation and self-assessment are an indicator of the analytical component’s formation; ability to adjust the results of professional and pedagogical activity; knowledge of evaluation of the achieved results.
Структурні компоненти формування готовності майбутніх бакалаврів з фізичної культури і спорту до тренерської діяльності
У статті на основі аналізу наукової літератури визначено структурні компоненти формування готовності майбутніх бакалаврів з фізичної культури і спорту до тренерської діяльності, відповідні їм педагогічні функції та показники. До структурних компонентів віднесено: пізнавально-творчий, проектувально-діагностичний, організаційний, інформаційно-комунікаційний та аналітичний. Зазначено, що пізнавально-творчий компонент реалізується через навчальну, пізнавальну, дослідницьку, творчу функції. Інформаційно-комунікаційний компонент реалізується через інформаційну, комунікаційну, перцептивну, інтерактивну, сугестивну, стимулюючу функції. Проєктувально-діагностичний компонент реалізується через діагностичну, прогностичну, проєктувальну і моделюючу функції. Організаційний компонент реалізується через організаційну, управлінську, контролюючу, направляючу функції. Аналітичний компонент реалізується через: оцінну, аналітичну, коригувальну функції. Визначено, що загальною для всіх компонентів тренерської діяльності є рефлексивна функція. Зазначено, що показником сформованості пізнавально-творчого компонента є загально-педагогічні, спеціальні, тренерські знання; мотивація до навчально-пізнавальної діяльності; ціннісне ставлення до професійної діяльності; здатність до професійної творчості. Показником сформованості інформаційно-комунікаційного компонента є вміння дидактичної обробки навчального матеріалу; володіння методами виховання і навчання; стилями педагогічного спілкування. Показником сформованості проеєктувально-діагностичного компонента є вміння здійснювати спортивно-педагогічну діагностику, вміння проєктувати, конструювати і моделювати навчально-тренувальний процес. Показником сформованості організаційного компонента є вміння організовувати, спрямовувати, контролювати навчально-тренувальний процес; володіння спортивно-педагогічними технологіями; адекватна професійна оцінка і самооцінка; вміння коригувати результати професійно-педагогічної діяльності; володіння способами оцінки досягнутих результатів. Показником сформованості аналітичного компонента є адекватна професійна оцінка і самооцінка; вміння коригувати результати професійно-педагогічної діяльності; володіння способами оцінки досягнутих результатів.